Pengaruh Standar Operasional Prosedur Dan Kualitas Kehidupan Kerja (Quality Of Work Life) Terhadap Efektivitas Kerja: Studi Pada Universitas Perjuangan Tasikmalaya - Selji Salgangga; Ading Rahman Sukmara; Apri Budianto (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This research is motivated by several problems, including the low effectiveness of employee work at the University of Struggle Tasikmalaya, this is thought to be caused by the suboptimal implementation of SOPs carried out by the university so that employee work results are not in accordance with the provisions set. In addition, the quality of work life is less supportive so that there are still employees who have not been able to complete a job according to the time that has been set. The purpose of this study is to determine the effect of standard operating procedures and quality of work life on work effectiveness at the University of Struggle, Tasikmalaya City. This study used a descriptive method with a quantitative approach. The respondents in this study were 132 employees at the University of Struggle Tasikmalaya, so the author took samples using the simple random sampling technique so that the number of samples in this study was 57 people. Analysis was carried out on data collected from observations, interviews, and questionnaires. The data analysis stage began with validity tests, reliability, transformation of ordinal values ​​to intervals, and data analysis in a verifiable/quantitative manner. The results of the study indicate that: 1) Standard operating procedures have an effect on work effectiveness at the University of Struggle Tasikmalaya. This means that the better the implementation of standard operating procedures for all employees in the University of Struggle environment, the more effective the employees' work will be. 2) Quality of work life has an effect on work effectiveness at the University of Struggle Tasikmalaya. This means that the better the quality of work life at the University of Struggle, the more effective the work will be. 3) Standard operating procedures and quality of work life on work effectiveness at the University of Struggle, Tasikmalaya City. This means that the better the implementation of standard operating procedures and the better the quality of work life at the University of Struggle, the more effective the work will be.